Study of Drinking Water Quality for Some Water Purification Plants and Pipes Network in Mosul City - I. AL-Hamdany, Mawj R.; N. F., Mazin (Iraqi Journal of Science, 2023)
This study focusing on river water quality as a source of raw water, efficiencies of water treatment plants, the goodness of transporting water pipes in the water networks and drinking water quality as consumed within certain city residential sectors, in addition to seasonal variation. The following water quality parameters were studied: Electrical Conductivity, Turbidity, Dissolved oxygen, Biochemical oxygen demand, the concentration of nutrients like nitrogen and phosphate, the residual chlorine in addition to total bacterial count and total colon bacteria of raw water, and treated water of four selected water treatment plants in Mosul city. These plants are : the right united scheme, the new left scheme ,the old left scheme and the Ghezlani scheme and follow up analyzing water quality parameters in the lines till the very far ends at the water network covered by every treatment plant. The sampling points were selected at the beginning; the middle andthe end of the water transporting lines .The study extended over nine months period started in September , 2013 and ended at May , 2014. The studied water quality parameters at most exceed the international and the Iraqi national standards limits of water quality. These parameters include turbidity, phosphate and total bacterial count. In addition most of the analyzed water quality parameters of the city residential sectors were totally free of residual chlorine.